Adaptation of Diqing Tibetan pigs to hypoxic and cold environments through extramedullary hematopoiesis and uncoupled thermogenesis in the liver - Xinpeng Li; Xinxing Dong; Shuhong Zhao; Yunlong Ma; Siqi Jin; Chunlu Zhou; Yi Lan; Shuyuan Luo; Bin Ni; Hongjiang Wei; Dawei Yan (BMC Biology)
Abstract Background Tibetan pigs, which have long inhabited the Qinghai-Tibet Plateau at elevations exceeding 3000 m, serve as an ideal model for studying adaptation to extreme high-altitude environments. The multifunctionality of the liver (hematopoiesis, metabolism, detoxification) plays a crucial role in the adaptation of Tibetan pigs to hypoxic and cold environments, yet the specific mechanisms remain unclear. Results This study employed single-nucleus RNA sequencing to profile and conduct bioinformatic analyses on the liver tissues of Diqing Tibetan pigs across 5 developmental stages (embryonic day 25, embryonic day 55, day of birth, development to 30 days, and development to 90 days). The goal was to identify and investigate key cell types and the regulatory mechanisms of core gene expression that facilitate adaptation to hypoxia and cold. In the fetal liver, various subpopulations of erythrocytes were detected. Analysis of these subpopulations allowed for the construction of a cellular development trajectory from proliferative erythrocytes to division erythrocytes to denucleating erythrocytes, revealing that key transcription factors (JUNB and MAFF) and functional genes (HBP1 and PPP2CB) play significant roles in erythrocyte enucleation. Furthermore, the presence of hematopoietic stem cells in the postnatal liver was observed, with identification of subpopulations exhibiting myeloid differentiation tendencies. These cells continuously support hematopoiesis and facilitate new blood vessel formation, thereby increasing red blood cell counts to aid in the adaptation of Diqing Tibetan pigs to hypoxic conditions. Additionally, a class of hepatocytes capable of converting metabolic energy into heat through uncoupling processes was identified, which assists in the adaptation to the cold environments of the plateau. Conclusions In summary, our study provides new scientific perspectives on the adaptation mechanisms of high-altitude animals to extreme environments.